The Problem of Appropriate Psychology of Religion Measures for Non-Western Christian Samples with Respect to the Turkish-Islamic Religious Landscape - (:unkn) unknown (SAGE PUBLICATIONS LTD, 2012)
Despite the fact that Islam is the second largest religion in the world, empirical studies on Muslim religiosity have been very rare. The reason for this is seen in the lack of measurements applicable to Muslim samples. Nonetheless, the few empirical studies about Muslims, the role of Islam in terms of physical and psychological well-being, and comparative studies give rise to hope. The problems of application, adaptation and translation of religiosity and spirituality scales developed for Christian traditions is an issue that the psychology of religion in Turkey is facing but has not yet solved. This article shall provide an overview of the religious landscape in Turkey that has to be considered when applying Turkish or Western measures of religiosity to Turkish samples. Further problems in cross-cultural/religious studies due to inappropriate measures are illustrated. Finally religiosity scales developed and/or applied within the psychology of religion research in Turkey are listed.
Keywords: Turkey; Islam; Muslim; culture; religiosity; psychology; measurement; ORIENTATION; AGE